2018
DOI: 10.1585/pfr.13.1201099
|View full text |Cite
|
Sign up to set email alerts
|

Thomson Scattering Measurement of Two Electron Temperature Components in Transition to Detached Plasmas

Abstract: We have performed laser Thomson scattering (LTS) measurements during the transition between attached and detached helium plasmas in the linear divertor simulator NAGDIS-II. In the detached plasma, the LTS spectrum shows a discrepancy with a single Gaussian function. The discrepancy is resolved by the spectrum fitting with a sum of two Gaussian functions, indicating that the electron energy distribution contains two different temperature components.Detached plasma plays an essential role for magnetically confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…A comparison of plasma parameters in downstream shows the reduction rate of the static plasma pressure P s from upstream to downstream varies by 14 % to 0.45 % as ionizing plasma is changed to recombining plasma. We also found that two different temperature components [10] exists only in the downstream region of recombining plasmas.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…A comparison of plasma parameters in downstream shows the reduction rate of the static plasma pressure P s from upstream to downstream varies by 14 % to 0.45 % as ionizing plasma is changed to recombining plasma. We also found that two different temperature components [10] exists only in the downstream region of recombining plasmas.…”
Section: Resultssupporting
confidence: 54%
“…In the previous study, it was mentioned that two electron temperature components existed when the plasma state was in the transition from ionizing to recombining plasmas [10], suggesting that the two temperature components were attributed to fluctuations of plasma parameters. Figure 6 shows LTS spectrum and EEDF of downstream at P end = 6.5 mTorr, like the plasma state mentioned above.…”
Section: Two Different Temperature Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tendency that T ed and T e_LTS slightly increased at P n > 2.2 Pa was observed in Figure a. The recent spectroscopic and LTS study using NAGDIS‐II showed that two different temperature components could independently appear in time . The slight increase in T e might indicate that the high temperature component was dominant when P n > 2.2 Pa.…”
Section: Resultsmentioning
confidence: 85%